Gerakan Agama dan Politik di Mesir: Refleksi atas Ikhwān Al-Muslimīn dan Revolusi Pemuda Tahrir Square di Kairo - Muhammad Asrory Mulki; Herdi Sahrasad (ILMU USHULUDDIN, 2012)
Egyptian Revolution (Nile Revolution) in February 2011 was totally moved by the desire and struggle conducted by the Egyptian young people, without considering the tribal entity and identity, ethnic group, not even religion. The absence of Islamic yells and lack of significant role from Islamist groups, in the time of demonstration, indicated that the fascination of ‘ideological Islam’ has faded in the Pyramida country. In contrast, Muslim Arabian revolunionists did not anymore give priority to Islamic symbols in their socio- political great effort, other than to common values and ideals, i.e. democracy and freedom. This also occurred to Ikhwān al-Muslimīn movement, which is said now as completing a reformation of ideology and method. When previously the violation was their ultimate agenda in achieving the goal, whereas recently they have adopted a way of democracy. The experience of poltical-Islam depolitization in the country seemed to change Ikhwān al-Muslmīn to award superiority on negotiation and democracy.